Transition from Paris dosimetry system to 3D image-guided planning in interstitial breast brachytherapy - Wiercińska, Judyta; Wronczewska, Anna; Kabacińska, Renata; Makarewicz, Roman (Journal of Contemporary Brachytherapy, 2015)
Purpose : The purpose of this study is to evaluate our first experience with 3D image-guided breast brachytherapy and to compare dose distribution parameters between Paris dosimetry system (PDS) and image-based plans. Material and methods : First 49 breast cancer patients treated with 3D high-dose-rate interstitial brachytherapy as a boost were selected for the study. Every patient underwent computed tomography, and the planning target volume (PTV) and organs at risk (OAR) were outlined. Two treatment plans were created for every patient. First, based on a Paris dosimetry system (PDS), and the second one, imaged-based plan with graphical optimization (OPT). The reference isodose in PDS implants was 85%, whereas in OPT plans the isodose was chosen to obtain proper target coverage. Dose and volume parameters (D 90 , D 100 , V 90 , V 100 ), doses at OARs, total reference air kerma (TRAK), and quality assurance parameters: dose nonuniformity ratio (DNR), dose homogeneity index (DHI), and conformity index (COIN) were used for a comparison of both plans. Results : The mean number of catheters was 7 but the mean for 20 first patients was 5 and almost 9 for the next 29 patients. The mean value of prescribed isodose for OPT plans was 73%. The mean D 90 was 88.2% and 105.8%, the D 100 was 59.8% and 75.7%, the V PTV 90 was 88.6% and 98.1%, the VPTV 100 was 79.9% and 98.9%, and the TRAK was 0.00375 Gym–1 and 0.00439 Gym–1 for the PDS and OPT plans, respectively. The mean DNR was 0.29 and 0.42, the DHI was 0.71 and 0.58, and the COIN was 0.68 and 0.76, respectively. Conclusions : The target coverage in image-guided plans (OPT) was significantly higher than in PDS plans but the dose homogeneity was worse. Also, the value of TRAK increased because of change of prescribing isodose. The learning curve slightly affected our results.